Аналіз методів відеомонтажу в сучасній медіаіндустрії - Прокоф’єв, К. А. (ХНУРЕ, 2024)
Video editing is an integral part of the modern media industry, which plays a key role in creating high-quality and attractive content. This work explores the techniques and importance of video editing in the entertainment industry, emphasizing its ability to control the pace and rhythm of a story, reduce the length of footage, and strengthen brand identity. Well-edited videos have a better chance of engaging the audience and going viral on social media platforms. At the same time, the article presents various methods of video editing, such as linear and non-linear, which expand the possibilities of the creative process. Given the variety of media platforms and formats, editors should optimize content for each of them.
Keywords: відеомонтаж; медіаіндустрія